Perceived social norms of health behaviours and college engagement in British students. Issue 2 (4th March 2017) - McAlaney, John; Jenkins, William
Abstract : The social norms approach is an increasingly widely used strategy of behaviour and attitude change that is based on challenging misperceptions individuals hold about their peers. Research to date has been carried out predominately in the US college system, with a focus on substance use behaviours. The aim of the current study was to explore peer perceptions of both substance use and other behaviours in a British student sample, as the first step in determining whether the social norms approach may be applicable within Europe. Students at eight further education colleges in the UK were surveyed on their personal and perceived peer health and college engagement behaviours and attitudes by means of a printed and online survey. Respondents reported a perceived norm of frequency of substance use that was higher than the reported norm. Results relating to the injunctive norms of substance use were mixed but demonstrated that the majority of respondents do not actively approve of tobacco, cannabis or other drug use. Respondents also reported a norm of academic engagement that was more positive than the perceived norm of their peers. The results relating to substance use are consistent with work conducted in the US college system, despite the differences in culture and legislation. In addition, the results indicate that there may be similar misperceptions around other areas of health and college engagement. This suggests that the social norms approach may be a viable method of behaviour change in UK students.